Waste-to-energy conversion technologies in the UK: Processes and barriers – A review. (January 2021) - Foster, William; Azimov, Ulugbek; Gauthier-Maradei, Paola; Molano, Liliana Castro; Combrinck, Madeleine; Munoz, Jose; Esteves, Jaime Jaimes; Patino, Luis
Abstract: This paper reviews the sector of waste-to-energy looking at the main processes and feedstock involved. Within this, incineration, gasification, pyrolysis, anaerobic digestion and hydrothermal liquefaction are named and discussed. Through the discussions and scrutiny, manure is highlighted as a significant source of ammonia, methane, and nitrogen oxides emission, estimated to be 40%, 22.5% and 28% respectively of the total UK's anthropogenic emissions. Manure, and indeed the pollution it poses, are shown to remain largely ignored. In waste to energy processing, manure is capable of providing biogas for a number of pathways including electricity generation. Anaerobic digestion is highlighted as a suitable process with the crucial capability of drastically reducing the pollution potential of manure and slurry compared to no processing, with up to 90% reduction in methane and 50% reduction in nitrogen oxide emissions. If the majority of the 90 million tonnes of manure and slurry in the UK were to be processed through biogas harvesting, this could have the potential of producing more than 1.615 TWh of electricity. As such, the economics and legislation surrounding the implementation of anaerobic digestion for manure and slurry are discussed. In the end, restraining factors that limit the implementation of anaerobic digesters on farms in the UK are discussed. These are found to be mainly capital costs, lack of grants, insufficiently high tariff systems, rather than low gas yields from manure and slurry. Highlights: Lack of manure treatment in the UK results in 28% of all ammonia emissions. NOX emitted from agriculture accounts for 3% of the total NOX emissions in the UK. Manure and slurry contribute about 50% of anthropogenic UK's methane emissions. Drops in tariff rates result in fall in number of anaerobic digestion plants in UK. AD could produce 1.615 TWh electricity, i.e. 0.45% of total UK's annual demand.